The Effect of Image Potential on the Current-Voltage Characteristics of a Ferritin-layer - Eunjung Bang; Jong Bok Seo; Eui Kwan Koh; Kwon-Seok Chae (Journal of Analytical Science and Technology, 2010)
Considering for the concept of power storage systems, such as those used to supply power to microelectronic devices, ferritins have aroused a lot of interests for applications in bioelectrochemical devices. And electron transfer rates from the proteins to electrode surface are key determinants of overall performance and efficiency of the ferritin-based devices. Here we have investigated the electron transport mechanism of ferritin layer which was immobilized on an Au electrode. The current-voltage (I-V) curves are obtained by a conductive atomic force microscope (c-AFM) as a function of contact area between AFM tip and the ferritin layer. In the low voltage region, I-V curves are affected by both Fowler-Nordheim tunneling and image force. On the other hand, the experimental results are consistent with a Simmons model in a high voltage region, indicating that, as the voltage increases, the image potential has a dominant effect on the electron transport mechanism. These results are attributed to the film-like character of the ferritin layer, which generates an image potential to lower the barrier height in proportion to the voltage increment.